POLA DAN SENSITIVITAS KUMAN DI PENDERITA INFEKSI SALURAN KEMIH - Samirah Samirah; Darwati Darwati; Windarwati Windarwati; Hardjoeno Hardjoeno (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2006)
The bacterial and sensitivity pattern towards antimicrobials on urinary tract infections (UTI) patients are very important to beknown by clinicians to get a successful treatment. The bacterial and sensitivity pattern towards antimicrobials will be changed in differentplace and time, so that those should be analyzed routinely. To evaluate the bacterial and antimicrobials resistance pattern on urinarytract infections patients. A retrospective study on 220 urinary samples in January until December 2004 at Clinical Microbiology subunit of Dr.Wahidin Sudirohusodo hospital . Of 99 samples of UTI, Prevalence of UTI in woman (54.5%) were higher than man (45.5%).Most of sample (28 samples) were found in 0 to 15 years group. The most bacteries in urine were Escherichia coli (39.4%) and Klebsiella(26.3%). Amikacin was sensitive to all bacteries, while amoxicilin and ampicilin were resistance. Prevalence of UTI in women werehigher than in men. Incidens of UTI was highest in children group. The most bacteries in urine samples were Escherichia coli. Amikacinwas sensitive to all bacteries, while Amoxicilin and Ampicilin were resistance.